Evaluation of The Number of Rainy Days Observed for Long Years Due to Global Climate Change in Nevşehir /Turkey - Cüneyt BAGDATLI, M.; Arslan, Oguzhan (Recent Research in Science and Technology, 2019)
In this research caried out Nevsehir province, Avanos and Ürgüp districts of Turkey’s Central Anatolia Nevsehir. In the study, it is aimed to reveal the trends of years by changing the number of long year total rainy days by Mann Kendall and Sperman’s Rho correlation tests. Within the scope of the study, 34 years long total monthly rainy days data between 1986-2019, which were obtained from automatic meteorology stations, were evaluated. According to the results of the trend analysis, the average total number of rainy days in Nevşehir province was 77 days minimum, the maximum number of rainy days was 142 days, and the average of the average number of rainy days was 109 days. In Avanos district, the average number of rainy days for a long time was 57 days, and the maximum number of rainy days was 129 days, while the average of the number of rainy days for long years was 89 days. In Ürgüp district, the average number of rainy days for a long time was 65 days, the maximum number of rainy days was 129 days, and the average of the number of rainy days for long years was 95 days. As a result, considering the number of long year rainy days, it is concluded that there is no significant trend in Nevşehir province, Avanos and Ürgüp district stations.